Palynology of a coal seam in Karoo deposits of Botswana and correlation with southern African coal-bearing strata - Barbolini, Natasha (My University, 2010)
A significant amount of palynological work has been done on southern African coal seams in the Ecca Group, but as yet there is little consensus on how these areas relate to each other. This study investigated the palynology of a coal seam from Mmamantswe (Mmamabula area), Botswana, approximately 70 km north-east of Gaborone. A total of 124 samples were taken from two borehole cores and subjected to acid preparation, oxidation and acetolysis. Coal samples were found to be barren of palynomorphs. Fifty carbonaceous mudstones and siltstone samples yielded twenty-two productive samples. A thermal alteration index of 3.0-3.5 was assigned for the sediments. Palynomorph diversity was high, with 64 genera and 90 species present, dominated by trilete and alete spores. This indicates a parent flora of mostly lower order lycopods, sphenophytes and ferns. Non-taeniate bisaccate and monosaccate pollens were scarce, and striates extremely rare (only two species), suggesting an autochthonous origin for the coal swamp. The Mmamantswe core was sub-divided into five microfloral assemblage zones. A transition from monosaccate dominance in the lower part of the core, to equal numbers of monosaccates and non-taeniate bisaccates in the upper part of the core, was seen. As the Mmamantswe palynoflora possesses elements of both the Late Carboniferous glacial floras and the mid-Permian coal floras, it is thought to represent a cross-over assemblage dating to soon after the Permo-Carboniferous boundary (Sakmarian and Early Artinskian). The Mmamantswe assemblage can be correlated with Assemblage Zones II and III of Falcon (1975a); Biozones B and C of MacRae (1988); and Zones 1, 2 and 3 of Anderson (1977) but does not fit well into any existing biozonation. The Mmamantswe palynoflora was most similar to that of Milorgfjella, Dronning Maud Land, Antarctica (Larrson et al. 1990) and the No. 2 Seam, Witbank, South Africa (Falcon 1989). Taphonomic controls on palynomorph preservation suggest that future studies should also attempt to focus on Permian sediments not containing coal, as microfloral assemblages from coal seams tend to be autochthonous, and subject to local climatic influences. Accordingly they are not as useful for inter-basinal correlation across Gondwana.
Keywords: palynology; coal; Karoo; stratigraphy; Botswana; Gondwana; Permian